Case Report: A Case of Intestinal Behçet's Disease Exhibiting Enhanced Expression of IL-6 and Forkhead Box P3 mRNA After Treatment With Infliximab - Yoshikawa, Keisuke; Watanabe, Tomohiro; Sekai, Ikue; Takada, Ryutaro; Hara, Akane; Kurimoto, Masayuki; Masuta, Yasuhiro; Otsuka, Yasuo; Yoshikawa, Tomoe; Masaki, Sho; Kamata, Ken; Minaga, Kosuke; et al. (Frontiers in Medicine, 2021)
Behçet’s disease (BD) is a rare inflammatory condition characterized by oral and genital ulcers, skin lesions, as well as ophthalmological, neurological, and gastrointestinal manifestations. BD involving the gastrointestinal tract is known as intestinal BD. The mucosa of the gastrointestinal tract of patients with intestinal BD exhibits enhanced levels of proinflammatory cytokines, such as IL-1beta, IL-6, and TNF-α. These proinflammatory cytokines play pathogenic roles in the development of BD, as evidenced by the fact that biologics targeting these cytokines effectively induce BD remission. It should be noted, however, that the molecular mechanisms by which the blockade of these cytokines suppresses chronic inflammatory responses in BD are poorly understood. Herein, we report a case of intestinal BD resistant to prednisolone that was successfully treated with infliximab (IFX). The induction of remission by IFX was accompanied by a marked elevation of IL-6 and forkhead box P3 (FOXP3) at mRNA level. This case suggests that induction of remission by IFX is mediated not only by the suppression of TNF-α-mediated signaling pathways, but also by the promotion of IL-6 expression and accumulation of regulatory T cells expressing FOXP3.